2016
DOI: 10.1038/onc.2016.198
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rewiring in melanoma

Abstract: Oncogene-driven metabolic rewiring is an adaptation to low nutrient and oxygen conditions in the tumor microenvironment that enables cancer cells of diverse origin to hyperproliferate. Aerobic glycolysis and enhanced reliance on glutamine utilization are prime examples of such rewiring. However, tissue of origin as well as specific genetic and epigenetic changes determines gene expression profiles underlying these metabolic alterations in specific cancers. In melanoma, activation of the MAPK pathway driven by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 133 publications
(180 reference statements)
2
150
0
2
Order By: Relevance
“…Our data support a model in which cells growing under PPSS become multidrug resistant due to rewiring of signaling pathways involved in the regulation of important proteins for chemoresistance (MDR1 and ABCG2) and survival (Bcl‐2). Rewiring of signaling networks has been demonstrated during oxidative stress (Garcia et al, ) as well as an adaptation mechanism to low nutrient and oxygen conditions (Ratnikov et al, ). We provide evidence that PPSS may induce or strengthen crosstalk between MDR1, ABCG2, and Bcl‐2 that are negligible or non‐existent in cells growing under RCC.…”
Section: Resultsmentioning
confidence: 99%
“…Our data support a model in which cells growing under PPSS become multidrug resistant due to rewiring of signaling pathways involved in the regulation of important proteins for chemoresistance (MDR1 and ABCG2) and survival (Bcl‐2). Rewiring of signaling networks has been demonstrated during oxidative stress (Garcia et al, ) as well as an adaptation mechanism to low nutrient and oxygen conditions (Ratnikov et al, ). We provide evidence that PPSS may induce or strengthen crosstalk between MDR1, ABCG2, and Bcl‐2 that are negligible or non‐existent in cells growing under RCC.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have revealed that lactate might have serious effects on the tumor-infiltrating immune cells, and decrease their immune surveillance by various mechanisms [4,5].…”
Section: Original Papermentioning
confidence: 99%
“…Although the Warburg effect is considered the basic feature of metabolic reprogramming, a large amount of evidence suggests that tumour cells rely on both mitochondrial metabolism and glycolysis . Previous studies have shown that BRAF V600E is involved in melanoma metabolic reprogramming . Haq et al .…”
Section: Introductionmentioning
confidence: 99%